School - Based Management Prospects and Challenges: A Case of Public Secondary Schools in Murang’a South District, Kenya - Kiragu, Joyce Wangari; King’oina, John Ogamba; Migosi, Joash A (International Journal of Asian Social Science, 2013)
The main purpose of this study was to find out what the principals and teachers perceived were the prospects of school-based management (SBM), the accrued benefits of SBM and challenges schools would experience if SBM was introduced in Murang’a South district. The study adopted descriptive survey design. Stratified sampling was used to select 16 schools which participated in this study. A sample of 80 respondents was selected to participate in the study. The sample for the study included 64 teachers and 16 principals. Data for this study was collected using structured questionnaires which were administered by the researcher to a sample of principals and teachers in each of the sampled schools. A pre-testing of the research tools was carried out in four institutions which were not included in the study to ascertain validity and reliability of the instrument. The data was analysed manually and was presented in descriptive statistical tables using frequencies and percentages. The result of findings indicated that the introduction of SBM would be a way of addressing the current crisis in management of secondary schools, bringing about accountability, commitment by teachers in discharging their duties, efficient use of resources, timely syllabus coverage, delivery of quality education, improve efficiency and reduce need for supervision among other prospects if it was introduced in secondary schools in the district. The study made the following recommendations: Firstly, principals and teachers should be actively involved in making decisions about secondary schools management because they are the people on the ground and understands the school environment better. Secondly, the Ministry of Education should consider involving all the education stakeholders in formulating policies, this way they will own the policies and it will be easy to implement them without being seen like they are forcing them on schools.